Factors Influencing The Adoption of E-Government in Riau Province - Debora Sri Intan; Lily Purwianti; Hepy Hefri Ariyanto; Ratih Anggraini (Dinasti Publisher, 2025)
The goal of this research is to identify the elements that affect the implementation of e-government in Riau Island. Employees of the Riau Islands Provincial Government comprise the sudy population, and the research sample consists of those emplyoees who meet the requirements of being able to use digital public service applications in the course of their work. An online survey with measurement questions was sent to respondents in existing regional apparatus organizations and complete answers were received by 417 respondents consisting of permanent and non-permanent employees with variations in education and age, were considered usable for analysis. Trust, security concern, perceived usefulness, information communication and technology, perception of e-government as a mediating variable and adoption of e-government as a dependent variable are the variables in this study, which employs a quantitavive research methodology with data processing using Samrt Pls. Results indicate that trust, security concern, perceived usefulness, information communication and technology have an effect on user decisions in adopting the e-government system. The findings of this study can be considered by the-government when formulating policies that can promote and anhance system quality and establish a thorough and high-quality e-government system implementation while simultaneously enhancing data secutity and the accessibility of sufficient technology infrastructure in the provincial government of Riau Island’s workplace.